Detection Of Sliding Plane as A Disaster Mitigation Efforts In The Pengembur Village, Pujut Sub District, Central Lombok Regency - Elinda, Baiq Ulfa Putri; Al Fatari, Hotinul; Marzuki, Marzuki; Sukrisna, Bakti; Alaydrus, Alfina Taurida; Minardi, Suhayat (Institut Teknologi Bandung, 2020)
A landslide disaster is a threatening disaster every time coming of the rainy season. Landslide potency can be detected on the surface through the form of topography and vegetation and beneath the surface of the rock layers former. From the type of rock the former can be known existence of the sliding plane which is the place of the sliding material. Research has been conducted to detect the plane of slide based on the resistivity value and the shear wave speed by using geoelectric and seismic method in Pengembur village, sub district of Pujut, Central Lombok regency. The result of analysis shows that the rocks layer former in the area consist of low cohesion soil deposits, weathered clay soils, water-saturated sand, and unconsolidated sand which has a thickness (3.7 – 4.0) meters. The field of sliding plane is detected as a layer of clay with landslides potency towards the west with the translation slide type